The Osteogenic Capacity of HumanAmniotic Membrane Mesenchymal Stem Cell (hAMSC) and Potential for Application in Maxillofacial Bone Reconstruction in Vitro Study - Kamadjaja, David (Stem Cell Research and Development Center, Universitas Airlangga, 2020)
Amniotic membrane of human placenta is a source of abundant mesenchymal stem cell (hAMSC) which makes it a potential source of allogeneic multipotent cell for bone healing. However, much has to be explored about its isolation procedure and the osteogenic differentiation potential. The aims of this study are to establish the procurement procedure of human amniotic membrane, the isolation and culture of hAMSC, the MSC phenotypic characterization, and the in vitro osteogenic differentiation of hAMSC. Results of the study are as follows. The quality of human amniotic membrane would be best if procured from Caesarean operation under highly aseptic condition to avoid fungal and bacterial contamination on the culture. Isolation procedure using modified Soncini protocol yielded large amount of MSC with high proliferative capacity in culture medium. Characterization of hAMSC showed that the majority of the target cells exhibited specific MSC markers (CD10S and CD90) with a small number of these cells expressing CD45the marker of hematopoeitic cells. The in vitro osteogenic differentiation of hAMSC followed by Alizarin Red staining showed that osteoblastic differentiation was detected in a significantly high number of cells. This study concludes that hAMSCs isolated from human amniotic membrane have the capacity for in vitro osteogenesis which makes them be one of the potential allogeneic stem cells for application in maxillofacial bone reconstruction.